Exosomal tumor microRNA modulates premetastatic organ cells - Rana, Sanyukta; Malinowska, Kamilla; Zöller, Margot (Neoplasia, 2013)
Tumor exosomes educate selected host tissues toward a prometastatic phenotype. We demonstrated this for exosomes of the metastatic rat adenocarcinoma BSp73ASML (ASML), which modulate draining lymph nodes and lung tissue to support settlement of poorly metastatic BSp73ASML-CD44v4-v7 knockdown (ASML-CD44vkd) cells. Now, we profiled mRNA and microRNA (miRNA) of ASMLwt and ASML-CD44vkd exosomes to define the pathway(s), whereby exosomes prepare the premetastatic niche. ASML exosomes, recovered in draining lymph nodes after subcutaneous injection, preferentially are taken up by lymph node stroma cells (LnStr) and lung fibroblasts (LuFb) that were chosen as exosome targets. ASMLwt and ASML-CD44vkd exosomes contain a restricted mRNA and miRNA repertoire that differs significantly between the two lines and exosomes thereof due to CD44v6 influencing gene and miRNA transcription/posttranscriptional regulation. Exosomal mRNA and miRNA are recovered in target cells, where transferred miRNA significantly affected mRNA translation. Besides others, this was exemplified for abundant ASMLwt-exosomal miR-494 and miR-542-3p, which target cadherin-17 (cdh17). Concomitantly, matrix metalloproteinase transcription, accompanying cdh17 down-regulation, was upregulated in LnStr transfected with miR-494 or miR-542-3p or co-cultured with tumor exosomes. Thus, tumor exosomes target non-transformed cells in premetastatic organs and modulate premetastatic organ cells predominantly through transferred miRNA, where miRNA from a metastasizing tumor prepares premetastatic organ stroma cells for tumor cell hosting. Fitting the demands of metastasizing tumor cells, transferred exosomal miRNA mostly affected proteases, adhesion molecules, chemokine ligands, cell cycle- and angiogenesis-promoting genes, and genes engaged in oxidative stress response. The demonstration of function-competent exosomal miRNA in host target cells encourages exploiting exosomes as a therapeutic gene delivery system.
Available online 3 March 2014
Gesehen am 14.12.2021